2020
DOI: 10.5194/tc-14-3785-2020
|View full text |Cite
|
Sign up to set email alerts
|

The firn meltwater Retention Model Intercomparison Project (RetMIP): evaluation of nine firn models at four weather station sites on the Greenland ice sheet

Abstract: Abstract. Perennial snow, or firn, covers 80 % of the Greenland ice sheet and has the capacity to retain surface meltwater, influencing the ice sheet mass balance and contribution to sea-level rise. Multilayer firn models are traditionally used to simulate firn processes and estimate meltwater retention. We present, intercompare and evaluate outputs from nine firn models at four sites that represent the ice sheet's dry snow, percolation, ice slab and firn aquifer areas. The models are forced by mass and energy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 85 publications
(100 reference statements)
3
59
0
1
Order By: Relevance
“…These results therefore emphasise the importance of adequate spin-up and assessment of the effects of snowpack spin-up in producing and using SMB in Antarctica. Vandecrux et al (2020b) found that the Fixed version smoothes the firn density profiles, when compared to the dynamical version, this is confirmed by our results. One of the criteria for the dynamical version is that it prefers to merge layers deeper than 5 m of w.eq., meaning that the top 5 m w.eq.…”
Section: Evaluation Against Observationssupporting
confidence: 90%
See 1 more Smart Citation
“…These results therefore emphasise the importance of adequate spin-up and assessment of the effects of snowpack spin-up in producing and using SMB in Antarctica. Vandecrux et al (2020b) found that the Fixed version smoothes the firn density profiles, when compared to the dynamical version, this is confirmed by our results. One of the criteria for the dynamical version is that it prefers to merge layers deeper than 5 m of w.eq., meaning that the top 5 m w.eq.…”
Section: Evaluation Against Observationssupporting
confidence: 90%
“…have a high vertical resolution, this makes it easier to detect changes in density. In areas such as the AP, Ronne-Filchner ice shelf, Ross ice shelf and in coastal areas of Dronning Maud Land where seasonal melt occurs (Zwally and Fiegles, 1994;Wille et al, 2019), meltwater can percolate into the firn and refreeze, creating ice lenses that change the density, but that cannot be detected if the subsurface scheme have layers with a fixed mass even if the vertical resolution is increased (Vandecrux et al, 2020b). Not only is there a difference between the models when evaluating density profiles, this study also shows the importance of spatial evaluation, here the three simulations follow the same pattern by over/underestimating the densities in the same areas (Fig.…”
Section: Evaluation Against Observationsmentioning
confidence: 99%
“…This period is chosen to match the long-term altimetry record of Shepherd et al (2019), hence facilitating intercomparison of observed elevation changes and modelled firn thickness change experiments of this study. We limit our analysis to the EAIS because surface melt there is minor compared to the AP and WAIS, and FDM fidelity remains questionable for simulating wet firn compaction, water percolation and refreezing (Steger et al, 2017;Verjans et al, 2019;Vandecrux et al, 2020). Table 1: The nine firn densification models (FDM), three regional climatic models (RCM) and two surface density parameterisations ( ) used in this study.…”
Section: Ensemble Configurationmentioning
confidence: 99%
“…This period is chosen to match the long-term altimetry record of Shepherd et al (2019), hence facilitating intercomparison of observed elevation changes and modelled firn thickness change experiments of this study. We limit our analysis to the EAIS because surface melt there is minor compared to the AP and WAIS, and FDM fidelity remains questionable for simulating wet firn compaction, water percolation and refreezing (Steger et al, 2017;Verjans et al, 2019;Vandecrux et al, 2020). 1: The nine firn densification models (FDM), three regional climatic models (RCM) and two surface density parameterisations ( ) used in this study.…”
Section: Ensemble Configurationmentioning
confidence: 99%